Letter to the right honourable the chancellor of the exchequer, illustrative of the operation and effect of the corn restriction laws upon landed property, and the probable consequences of their abrogation to landowners and the public (Oliver and Boyd [etc.], 1826)
Chancellor of the exchequer is Frederich John Robinson, 1st Earl of Ripon.